PEMANFAATAN WADUK MRICA SEBAGAI SUMBER BELAJAR OUTDOOR STUDY MATA PELAJARAN GEOGRAFI DI SMA NEGERI WANADADI KABUPATEN BANJARNEGARA (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2016)
Using dam as a source of learning geography same with the environment as a source of learning. Outdoor learning study is learning outside of class or environment around carrying students see direct object to be researched.This research aims to make the students know the utilization of Dam Mrica as a source of learning methods outdoor study and learning outcomes cognitive on the subject matters matter the hidosfer X class school 1 Wanadadi year 2014/2015. Data collection techniques used on research is a technique observation, documentation, and tests.The population research were those coming class a class X schools 1 Wanadadi which totaled 288 students.The sample collection technique used is a technique of sampling purposive namely under the terms of certain, samples to be taken was a class X- 9 with the number of 32 students as respondents class experiment.Of the resuls of data analysis showed that the interest of students towards learning by utilizing Mrica dam as a source of higher leaning with a declared value of 86,6, while the activity of students in both affective and psychomotor expressed high with a value 77,7 and 82,9. The average student leaning outcomes in experimental class wihich originally 59,18 increase to 80,50. The results showed an increase in the results of cognitive learning, affective and psychomotor so it can be concluded that leaning by utilizing Mrica dam as a ssource of learning can be applied as an alternative geography of learning outside the classroom effectively